2008
DOI: 10.1038/nature07281
|View full text |Cite
|
Sign up to set email alerts
|

Agrochemicals increase trematode infections in a declining amphibian species

Abstract: Global amphibian declines have often been attributed to disease, but ignorance of the relative importance and mode of action of potential drivers of infection has made it difficult to develop effective remediation. In a field study, here we show that the widely used herbicide, atrazine, was the best predictor (out of more than 240 plausible candidates) of the abundance of larval trematodes (parasitic flatworms) in the declining northern leopard frog Rana pipiens. The effects of atrazine were consistent across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
386
5
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 409 publications
(423 citation statements)
references
References 24 publications
30
386
5
2
Order By: Relevance
“…Past amphibian studies have also suggested scenarios that may lead to evolutionary responses to parasites. For example, high‐nutrient agricultural run‐off may indirectly facilitate trematode abundance by increasing the amount of algal resources available to the first intermediate hosts (snails) of trematodes (Koprivnikar & Redfern, 2012; Koprivnikar et al., 2006; Rohr, Schotthoefer, et al., 2008). Higher abundances of Echinoparyphium may select for increased resistance or tolerance to Echinoparyphium in amphibian populations near agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…Past amphibian studies have also suggested scenarios that may lead to evolutionary responses to parasites. For example, high‐nutrient agricultural run‐off may indirectly facilitate trematode abundance by increasing the amount of algal resources available to the first intermediate hosts (snails) of trematodes (Koprivnikar & Redfern, 2012; Koprivnikar et al., 2006; Rohr, Schotthoefer, et al., 2008). Higher abundances of Echinoparyphium may select for increased resistance or tolerance to Echinoparyphium in amphibian populations near agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that, to thoroughly understand climatic effects on Bd-related declines, investigators will need to explicitly test how climate affects interactions between Bd and amphibian hosts, as well as consider other factors altering host-parasite dynamics or host fitness directly (39,(42)(43)(44). Additionally, the influence of climate on amphibians will almost certainly depend on the local scales at which organisms experience climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Pesticides have the potential to increase susceptibility (Mann et al, 2009) while elevated nutrient concentrations have the potential to increase the incidence of disease in amphibian populations (Johnson et al, 2007). On the other hand, studies have documented the relationship between pesticides and susceptibility to infections by trematodes (Rohr et al, 2008). These parasitic infections have the potential to negatively impact populations causing malformations (Reeves et al, 2013) which can lead to impaired mobility, decreased food intake, and an increased susceptibility to predators (Blaustein and Johnson, 2003).…”
Section: Potential Impacts To Amphibiansmentioning
confidence: 99%
“…Increased eutrophication due to nitrogen based fertilizers, coupled with pesticide application, may cause trophic cascades resulting in increased rates of parasitism in wetlands and has been linked to immunosuppression in amphibians (Brodkin et al, 2007;Johnson et al, 2007). Although a direct link has been made between pesticide exposure and infection by trematodes (Rohr et al, 2008;Kiesecker, 2002), a general understanding of these interactions in the field is lacking because results vary by species and land-use (King et al, 2007).…”
Section: Introductionmentioning
confidence: 99%